A Conceptual Model Exploring the Emergence of Consumer Xenocentrism: The Role of Antecedents and Disidentification. Issue 2 (15th March 2023) - Jiang, Chuandi; Christian, Ronald G.
Abstract: The purpose of this conceptual paper is to develop a theoretical framework that identifies antecedents for the emergence of consumer xenocentrism (C-XEN). Blending perspectives from social identity theory and dependency theory, a conceptual framework is developed to illustrate the emergence of C-XEN. The framework specifies social, cognitive, and affective antecedents of C-XEN, and proposes that disidentification mediates the relationship between the antecedents and the emergence of C-XEN. The framework provides a comprehensive understanding of the circumstances under which xenocentric attitudes emerge, enhance, and lead to a favorable bias toward foreign products. Testable propositions are discussed to stimulate future research.